Abstract - SHARMA, PRADEEP (Journal of Cereal Research, 2019)
Abstracts of 4th Internatonal Group Meeting on " Wheat Productivity Enhancement through Climate Smart Practices" at CSK HPKV, Palampur, HP, India (February 14-16, 2019)